Pengaruh Pengawasan Fungsional Terhadap Pengelolaan Keuangan Daerah pada Inspektorat Provinsi Gorontalo - Mahfiza Mahfiza (Al-Buhuts, 2016)
This study aims to determine the influence of functional supervision (X), which includes examination (X1), Test (X2), Investigation (X3) and Assessment (X4) either simultaneously or partially on financial management (Y) Province of Gorontalo.The research methodology used is quantitative method and sampling by sampling census technique on 75 votes government internal supervisory apparatus at inspectorate office Province of Gorontalo.The results showed that: (1) The control function (X) which includes: Examination (X1), Test (X2), Investigation (X3) and Assessment (X4) simultaneously positive and significant impact on the local financial management (Y) of Gorontalo Province, As much as 73,9% and the remaining 26,1% is influenced by other variables that have not been studied, for example, a performance variable, and effectiveness of financial management. Partially, (1) Examination (X1), positive and significant impact on the local financial management (Y)to 26,9% (2). Testing (X2) positive and significant impact on the local financial management (Y) of Gorontalo Province amounted to 17,4%. (3) Investigation (X3), partially positive and significant impact on the local financial management (Y) of Gorontalo Province amounted to 31,8% and Assessment (X4), partially positive and significant impact on the local financial management (Y) of Gorontalo Province is 27,4%.